Adherence to home blood pressure monitoring depending on the frequency of blood pressure measurements during the day - Voloshyna, Olena; Samorukova, Viktoriia; Dychko, Tetiana; Balashova, Iryna; Naidyonova, Olena; Chaika, Anna; Voloshyn, Andrii; Gushcha, Sergey (Journal of Education, Health and Sport, 2020)
The article analyzes the adherence to home blood pressure monitoring (HBPM) with different measurement frequency during the day in 90 patients with hypertension. It was found that after 2 weeks of blood pressure monitoring the greatest was patients' adherence to blood pressure measurement at home once (96.7%) or 2 times a day (90.0%), the lowest - at home pressure measurement every 2– 3 hours during the day (76.6%).The adherence to frequent HBPM (2-3 hours during the day) appeared to be significantly less compared to HBPM once or twice daily, due to more frequent violations of HBPM. Regardless of the frequency of measurements at HBPM, adherence to monitoring is most commonly impaired in working men, compared with women of similar age and employment.